Administrative Burden in BKD (Regional Civil Service Agency) Central Java Province, Indonesia - Maulana, Adam Surya; Dhani Ardiansyah (HM Publisher, 2024)
Efforts by the Regional Civil Service Agency (BKD) of Central Java Province aims to improve public services and the operational efficiency of the state civil apparatus. Based on data related to primary and secondary law, legislation and policy, this research uses a qualitative normative juridical approach. This research emphasizes several important points, including improve public service quality and operational efficiency of state civil servants; BKD's efforts to improve services through the placement of employees in accordance with their competencies; implementation of SINAGA to improve personnel administration; and the performance of the Central Java BKD. strategic planning for the future that focuses on the industrial revolution 4.0. This study shows that BKD Central Java is trying to improve service quality by increasing employee competency, providing adequate facilities and infrastructure, and utilizing information technology by introducing the SINAGA application. However, there are several obstacles and difficulties to overcome, such as a lack of adequate human resources and difficulties related to changing regulations. The Central Java Province BKD must continue to develop innovation and technology for personnel administration, strengthen a fair performance evaluation system, and ensure that employee needs are met. With this improvement, it is hoped that personnel services in this field will continue to improve.